Contribution of the Bit Torrent in Current Technology: A Study (International Journal of Food and Nutritional Sciences, 2022)
This study extensively examined the main topologies of several complicated systems that evolved from BitTorrent swarms. Our findings of the study suggest that the initial stage is not a good predictor of the ultimate result since the networks exhibit fundamental differences at different stages of a swarm. We also find a power-law posterior probability in the collaborative network that might not be choked through other peers, which points to the presence of a robust scale-free network. In contrast to previous studies, researchers are unable to definitively pinpoint continuous clustering in any of the networks, eliminating the idea of a small world that would be helpful for peer-to-peer downloads. These results suggest a fascinating area where BitTorrent's effectiveness may be improved. The author provides an early clustering solution for BitTorrent. This approach has theoretical backing, alters the tracker very minimally, and uses several simulations and experiments to demonstrate its effectiveness.